PENYUSUNAN ARAHAN STRATEGI DAN PRIORITAS PENGEMBANGAN PERBATASAN ANTAR NEGARA DI PROVINSI KALIMANTAN BARAT - Enni Lindia Mayona; S Salahudin; Rahmi Kusmastuti (TATALOKA, 2011)
The government’s development planning which concentrates to the security affairs not to the region’s prosperity shows a tendency that most of border regions are the forgotten ones. The plans for developing the west Kalimantan border regions have been compiled since 2002, however, most of them have not emerged into a realization. It is caused due to a requirement of huge amount of finance and limited availability of the finance source. At the first, a border region emphasizes the security affairs merely; consequently the development process has not been conducted well and ignored its people’s prosperity. The purpose of this research is to determine the strategy direction and priority for developing internations border regions in the province of West Kalimantan based on the condition of 15 (fifteen) districts which directly have a border with Malaysia (Sarawak), they are District of Paloh, District of Sajingan Besar, District of Jagoi Babang, District of Entikong, District of Sekayam, District of Ketungau Hulu, District of Ketungau Tengah, District of Putussibau, Kedamin, Puring Kencana, Empanang, Badau, Batang Lupar, and Embaloh Hulu. The analysis applied here is a descriptive analysis with an approach of qualitative and quantitative data using SWOT analysis and Analytical Hierarchy Process (AHP).The determination of a priority of region development is using variables connected with the development of West Kalimantan Region, which are variables of social, economy, and physic. The result of this research shows that facilities and infrastructure become a significant priority to develop the region borders of West Kalimantan.